Autologous Chondrocyte Implantation in Osteoarthritic Surroundings: TNFα and Its Inhibition by Adalimumab in a Knee-Specific Bioreactor. Issue 2 (February 2018) - Ossendorff, Robert; Grad, Sibylle; Stoddart, Martin J.; Alini, Mauro; Schmal, Hagen; Südkamp, Norbert; Salzmann, Gian M.
Background: Autologous chondrocyte implantation (ACI) fails in up to 20% of cases. Advanced intra-articular degeneration paired with an inflammatory environment may be closely related to implantation failure. Certain cytokines have been identified to play a major role during early osteoarthritis. Purpose: To investigate the effects of tumor necrosis factor α (TNFα) and its potential inhibition by adalimumab on cartilage regeneration in an in vitro model of ACI. Study Design: Controlled laboratory study. Methods: Bovine articular chondrocytes were cultivated and transferred at passage 3 to fibrin-polyurethane scaffolds. Constructs were loaded by compression (10%-20% scaffold height) and shear (±25°) in a fully characterized multiaxial load (L) bioreactor to simulate clinical ACI or were subjected to free swelling (FS) conditions for a duration of 2 weeks. TNFα (20 ng/mL), adalimumab (10 µg/mL), or both were added to the medium. To assess the outcome, DNA, GAG (glycosaminoglycan), and total collagen were quantified, and gene expression of anabolic (collagen 2, aggrecan, cartilage oligomeric protein, proteoglycan 4), catabolic (matrix metalloproteinases [MMP] 3 and 13), dedifferentiation (collagen 1), and hypertrophy (collagen 10) markers and proinflammatory cytokines (TNFα, IL-1β) was analyzed. Histological evaluation was performed with safranin O/fast green, toluidine blue, and immunohistochemistry of collagen 1 and 2. Apoptosis was analyzed by immunolabeling of anti-active caspase 3. For statistical evaluation, nonparametric tests were chosen with a significance level of P < .05. Results: A general downregulation of anabolic and upregulation of catabolic markers was detected in the TNFα groups. Collagen 2 was suppressed by TNFα (FS, P = .029; L, P = .006), while MMP 3 was significantly upregulated (FS, P = .035; L, P = .001). Dynamic loading induced a chondrogenic response, which could not fully antagonize the effect of the cytokine. Adalimumab antagonized all effects of TNFα. The histological and immunohistochemical assessments demonstrated less matrix formation in the cytokine-only groups. TNFα induced apoptosis, and this effect was increased by loading. Conclusion: TNFα does negatively affect chondrogenesis under simulated ACI conditions. Both dynamic load and, more potentially, adalimumab showed the capability of antagonizing the negative effects. Clinical Relevance: Catabolic cytokine suppression (ie, TNFα inhibition) combined with compression and shear load may best meet the conditions for chondrogenesis in an osteoarthritic environment.